A STUDY OF POLITENESS STRATEGIES USED BY ERIN GRUWELL IN FREEDOM WRITERS MOVIE - Leihitu, Sharly Prisca Maria; Triprihatmini, Veronica (International Journal of Humanity Studies (IJHS), 2021)
This study aims to identify and describe the four politeness strategies and the factors which are proposed by Penelope Brown and Stephen C. Levinson as seen in an American movie entitled Freedom Writers. It is qualitative research since the focus is on analyzing the utterances of the main character. The data is taken from the movie script. There are two research questions discussed in this study: (1) what are politeness strategies used by Erin Gruwell in the Freedom Writers movie? And (2) what factors influencing the politeness strategies? The findings show that Erin Gruwell applied the four politeness strategies, which are bald-on record, off-record, negative and positive politeness. However, the dominant strategy used by Erin is positive politeness, where Erin wants to get close and satisfy the hearer’s face. Related to the factors influencing the politeness strategies, the finding shows that there are two factors that affect Erin in choosing the politeness strategies: the payoffs and the sociological variables. In addition, sociological variables have three sub things: social distance, relative power, and rank of imposition.